2020
DOI: 10.3390/ijms21176228
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Dynamics, Identification, and Expression Patterns of Fatty Acid Synthase Genes in an Endoparasitoid, Meteorus pulchricornis (Hymenoptera: Braconidae)

Abstract: In insect parasitoids, fatty acid synthases (FASs) have received less attention and their roles associated with lipogenesis loss are far from clear. Meteorus pulchricornis is a solitary endoparasitoid wasp of many larvae of lepidopteran pests. The lipid content during developmental stages of M. pulchricornis was measured; it was higher in the larval and pupal stages but declined from six-day-old pupae. Lipid accumulation constantly decreased in the adult stage, even after feeding on honey solutions. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…No stop codons were found in any of the protein domains and ACC and FAS amino acid sequences of all these species aligned (Supplementary Texts 1 and 2 ), suggesting that these two critical genes for fat synthesis have been conserved throughout the repeated evolution of parasitism in insects. Further tests on these and other parasitoids are now needed to confirm plasticity of fat synthesis at the phenotypic level, but emerging results in other parasitoid systems, e.g., Nasonia species 23 and Meteorus pulchricornis 33 strengthen the notion that plasticity of fat synthesis may be the rule rather than the exception in parasitoids.
Figure 2 Conservation of two genes crucial for fatty acid synthesis in four parasitoid insects that supposedly had lost lipogenic activity.
…”
Section: Resultsmentioning
confidence: 91%
“…No stop codons were found in any of the protein domains and ACC and FAS amino acid sequences of all these species aligned (Supplementary Texts 1 and 2 ), suggesting that these two critical genes for fat synthesis have been conserved throughout the repeated evolution of parasitism in insects. Further tests on these and other parasitoids are now needed to confirm plasticity of fat synthesis at the phenotypic level, but emerging results in other parasitoid systems, e.g., Nasonia species 23 and Meteorus pulchricornis 33 strengthen the notion that plasticity of fat synthesis may be the rule rather than the exception in parasitoids.
Figure 2 Conservation of two genes crucial for fatty acid synthesis in four parasitoid insects that supposedly had lost lipogenic activity.
…”
Section: Resultsmentioning
confidence: 91%
“…No stop codons were found in any of the protein domains and ACC and FAS amino acid sequences of all these species aligned (Supplementary Texts 1 and 2), suggesting that these two critical genes for fat synthesis have been conserved throughout the repeated evolution of parasitism in insects. Further tests on these and other parasitoids are now needed to confirm plasticity of fat synthesis at the phenotypic level, but emerging results in other parasitoid systems, e.g., Nasonia species 24 and Meteorus pulchricornis 34 strengthen the notion that plasticity of fat synthesis may be more widespread in parasitoids.…”
Section: Resultsmentioning
confidence: 90%
“…With regard to the focus of studies on lack of lipid accumulation and parasitoid life histories, a key result of the study by Ruther et al ( 2021) is that their labeling experiments show very low isotope traces in the fatty acid fraction, suggesting that the Fatty Acid Synthase enzyme is functional in several parasitoids. This finding is not novel, however, because previous studies already showed that the fatty acid synthase (fas) gene is intact in several parasitoid species (Kraaijeveld et al, 2019;Visser et al, 2012Visser et al, , 2021 and its multiple paralogs are constitutively expressed in other species (Lammers et al, 2019;Visser et al, 2012;Wang et al, 2020), suggesting that fas plays a functional role in several aspects of the parasitoid's biology. The real conundrum, however, is the fact that while parasitoids may be capable of synthesizing fatty acids, the accumulation of storage lipids is not induced by sugar-feeding as it is in non-parasitoid insects.…”
mentioning
confidence: 79%